El Excentrico, 1965-05-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 05, 1965 [5 de mayo de 1965], Ano 15, No 14, Cover has a group photograph of Club Riviera's members with headline, "Club Riviera's Semi-Formal Saturday, May 15 Hawaiian Gardens."